Influence of the final temperature of investment healting on the tensile strength and Vickers hardness of CP Ti and Ti-6Al-4V alloy - Pedro César Garcia Oliveira; Gelson Luis Adabo; Ricardo Faria Ribeiro; Sicknan Soares da Rocha; Fabiano Araújo Ávila; Accácio Lins do Valle (University of São Paulo, 2007)
The aim of the work was to evaluate the influence of the temperature of investment healting on the tensile strength and Vickers hardness of CP Ti and Ti-6Al-4V alloy casting. Were obtained for the tensile strength test dumbbell rods that were invested in the Rematitan Plus investment and casting in the Discovery machine cast. Thirty specimens were obtained, fiftten to the CP Titanium and fifteen to the Ti-6Al-4V alloy, five samples to each an of the three temperatures of investment: 430ºC (control group), 480ºC and 530ºC. The tensile test was measured by means of a universal testing machine, MTS model 810, at a strain of 1.0 mm/min. After the tensile strenght test the specimens were secctioned, embedded and polished to hardness measurements, using a Vickers tester, Micromet 2100. The means values to tensile tests to the temperatures 430ºC, 480 and 530: CP Ti (486.1 - 501.16 - 498.14 -mean 495.30 MPa) and Ti-6Al-4V alloy (961.33 - 958.26 - 1005.80 - mean 975.13 MPa) while for the Vickers hardness the values were (198.06, 197.85, 202.58 - mean 199.50) and (352.95, 339.36, 344.76 - mean 345.69), respectively. The values were submitted to Analysis of Variance (ANOVA) and Tukey,s Test that indicate differences significant only between the materials, but not between the temperature, for both the materias. It was conclued that increase of the temperature of investment its not chance the tensile strength and the Vickers hardness of the CP Titanium and Ti-6Al-4V alloy.